Anti-obese effects of chitosan and psyllium husk containing vitamin C in Sprague-Dawley (SD) rats fed a high fat diet - Jung, Eun Young; Hong, Yang Hee; Chang, Un Jae; Suh, Hyung Joo (Progress in Nutrition, 2016)
We investigated whether vitamin C would enhance the anti-obese effects of chitosan and psyllium husk. The study was carried out with male Sprague-Dawley (SD) rats for 6 wk using the following diet groups. Normal diet (control), high fat diet (F-control), 5% chitosan (chitosan-1), 5% chitosan containing 1% vitamin C (chitosan-2), 10% psyllium husk (psyllium-1), and 10% psyllium husk containing 1% vitamin C (psyllium-2). Chitosan-2 (1.5%) showed a significant (p<0.05) decrease in epididymal fat pad weight as compared to F-control (2.3%) and chitosan-1 (2.1%). The epididymal fat pad weight of psyllium-2 (1.9%) was significantly (p<0.05) lower than that of F-control (2.3%). In conclusion, additions of vitamin C to chitosan and psyllium husk may be useful for reducing body fat.